2018
DOI: 10.1371/journal.pone.0197856
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between blood lead level and stunting, wasting and underweight- A cross-sectional study of children under 2 years-of-age in a Bangladeshi slum

Abstract: Elevated blood lead level (BLL) is known to cause cardiac, immune, and cognitive damage but had not been thoroughly studied in relation to stunting among children under two years of age. We primarily aimed to assess the relationship between elevated BLL, the accumulation of concerned amount of the metal lead in blood and stunting and secondarily—wasting and underweight amongst Bangladeshi children less than two years of age. For this cross-sectional study, BLL measurements, anthropometric data, and socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
2
10
0
1
Order By: Relevance
“…The population in this study had a higher prevalence of stunting, at 52.4%, compared to our urban population in Uganda (22.7%) and a lower median blood lead level at 4.2 μg/dL (IQR: 1.7-7.6) vs 5.8 μg/dL (4.5-7.7) in our Ugandan population. Another Bangladeshi study of 729 children under age 2 years in an urban slum environment, of which 39% were stunted and 86.6% had an elevated blood lead level (�5μg/dL), found no difference in blood lead levels between children who were stunted and those who were not [32]. In addition to childhood concurrent Pb level, prenatal Pb exposures have been associated with decreased https://doi.org/10.1371/journal.pone.0233108.g003…”
Section: Plos Onementioning
confidence: 98%
“…The population in this study had a higher prevalence of stunting, at 52.4%, compared to our urban population in Uganda (22.7%) and a lower median blood lead level at 4.2 μg/dL (IQR: 1.7-7.6) vs 5.8 μg/dL (4.5-7.7) in our Ugandan population. Another Bangladeshi study of 729 children under age 2 years in an urban slum environment, of which 39% were stunted and 86.6% had an elevated blood lead level (�5μg/dL), found no difference in blood lead levels between children who were stunted and those who were not [32]. In addition to childhood concurrent Pb level, prenatal Pb exposures have been associated with decreased https://doi.org/10.1371/journal.pone.0233108.g003…”
Section: Plos Onementioning
confidence: 98%
“…The negative impact of household food insecurity on childhood stunting was reported in Bangladesh (Alam et al, 2017;Mistry et al, 2019), where significant negative association between food insecurity and stunting among children under 2 years was documented. Other studies reported, however, that only severe food insecurity was significantly responsible for short stature in children (Choudhury et al, 2017;Raihan et al, 2018). Empirically, higher income enables households to secure adequate, diverse, frequent, and safe foods, and to ensure proper hygiene and sanitation that may result in a more enabling environment that leads to better nutrition among household members, specifically young children under 2 years of age.…”
Section: Associations Of Child Maternal and Household Characteristics With Stuntingmentioning
confidence: 99%
“…and Mistry et al(2019)documented a significant negative association between food insecurity and stunting among children under 2 years old. However, the other two studies that investigate according to the status of food insecurity, and they reported only severe food insecurity was responsible significantly for being short stature(Choudhury et al, 2017;Raihan et al, 2018) Mistry et al (2019). identified the quality of drinking water is not significantly associated with being short stature among children 0-2 years in Bangladesh.…”
mentioning
confidence: 93%